Квантово-фармакологічні властивості адреналіну - Небесна, Т.Ю.; Чекман, І.С. (Видавничий дім "Академперіодика" НАН України, 2007)
Adrenaline is a widely used drug in the medical practice. We study the quantum-pharmacological properties of adrenaline that is important for understanding the interaction between adrenergic drugs and adrenoreceptors. The geometry optimization for the adrenaline molecule was made by the PM3 method, Polak-Ribiere algorithm. We have determined the distances between atoms charges, electrostatic potential, total charge density, characteristics of molecular orbitals (HOMO, LUMO), and energetic properties of the adrenaline molecule.